Controlling Shareholder, Independent Commissioner, Board of Commissioner Characteristics, and Audit Committee on Tunneling Policy with Tax Avoidance as Control Variable - Titik Dwiyani; Purnomo Purnomo; Poniman Poniman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The aim of this research is to understand the affect of controlling shareholder, independent commissioner, board of commissioner characteristics, audit committee on tunneling policy with tax avoidance as control variable. The population and sample of the research is manufacture company of consumption good in industry sector which is registered in BEI in 2018 – 2020. The sample used stratified purposive sampling with 42 manufacture companies. Data analysis in this research used logistic regression analysis which is analyzed using SPSS 25. The result of coefficient determination test (Nagelkerke’s R Square) showed the value 35.2% and Goodness of Fit Test (Hosmer and Lemeshow Test) value showed 0.082. The result of logistic regression before putting control variable proved that controlling shareholder and commissioner characteristics affected positively significant, independent commissioner negatively significant, but audit committee proved unaffected on tunneling. The result of logistic regression after putting control variable of tax avoidance showed that controlling shareholder and commissioner characteristics variable were able to increase the significant affect on tunneling, but audit committee showed unaffected to tunneling and significant value decreased. However, independent commissioner did not change its signification. Keyword: GCG, controlling shareholder,tunneling, tax avoidance